Impact of COVID-19 on health research in New Zealand: a case study of a research-intensive campus. (31st May 2021) - Stamp, Lisa K.; Cameron, Vicky A.; Woodfield, Tim B. F.; Walker, Logan; Currie, Margaret; Templeton, Evie; Pilbrow, Anna P.; Tabakakis, Kosta; Phillips, Elisabeth; Lim, Khoon S.
ABSTRACT: The aim of this paper is to outline the impact Coronavirus disease (COVID)-19 has had on health research in New Zealand. We used data from the University of Otago, Christchurch, a research intensive satellite campus of the University of Otago with a large number of research only grant funded staff to highlight challenges and opportunities. All non-COVID-19 related laboratory and clinical research was suspended under New Zealand COVID-19 alert level 4 and the majority under level 3. To date, researchers predict that 95% of research projects have been affected. During the periods of lockdown research salaries continued to be paid from grants resulting in a 'salary gap' to support research staff (both academic and technical). Most funders have indicated there will be no additional funding to support researchers affected by the delays. Early and mid-career researchers have been particularly affected and are currently unable to travel for post-doctoral training and networking. A more robust career structure with adequate funding, particularly for early and mid-career researchers is required to ensure that New Zealand has a stable research work force to address the next health crisis.